THE PREVALENCE OF ANXIETY, DEPRESSION, AND SLEEP DISTURBANCES AMONG THE RHEUMATOID ARTHRITIS PATIENTS - Waheed, Zainab; Ume-kalsoom (Journal of Postgraduate Medical Institute, 2024)
Objective: To evaluate the prevalence of depression, anxiety and sleep disturbances among rheumatoid arthritis (RA) patients and gender disparities attending the outpatient clinics of a tertiary care hospital in Khyber Pakhtunkhwa, Pakistan. Methodology: The cross-sectional descriptive study was carried out on 250 patients visiting the orthopaedic OPD of teaching hospitals of Khyber Pakhtunkhwa from June 2022 to February 2023. A purposive sampling technique was used. Informed consent was taken from the patients. A questionnaire regarding anxiety, depression, and sleep disturbance was given to the patients. Data were collected using a pre-validated scale, Hospital Anxiety and Depression Scale (HADS). Results: The study included 250 patients with a mean age of 41.89 ± 7.82. Most of the patients were female (64.0%), and the average disease duration was 8.6 ± 6.2 years. Most of the patients belonged to middle-class families. On the HADS scale, females reported increased anxiety (p=0.001) along with the depression level (p=0.001) compared to males. Similarly, females experienced significantly more sleep disturbances (p=0.001). However, duration of the disease was not found to be associated with the prevalence of anxiety, depression, or sleep disturbances. Conclusion: Rheumatoid arthritis (RA) is linked with adverse impacts on psychological health. The results indicate that rheumatoid arthritis patients had comorbid anxiety, depression, and sleep disturbances. However, females are at higher risk of such comorbidities.